BCL11A enhancer dissection by Cas9-mediated in situ saturating mutagenesis - Canver, Matthew C.; Smith, Elenoe C.; Sher, Falak; Pinello, Luca; Sanjana, Neville E.; Shalem, Ophir; Chen, Diane D.; Schupp, Patrick G.; Vinjamur, Divya S.; Garcia, Sara P.; Luc, Sidinh; Kurita, Ryo; et al. (Nature (London), 2015)
Enhancers, critical determinants of cellular identity, are commonly recognized by correlative chromatin marks and gain-of-function potential, although only loss-of-function studies can demonstrate their requirement in the native genomic context. Previously, we identified an erythroid enhancer of human BCL11A , subject to common genetic variation associated with the fetal haemoglobin level, the mouse orthologue of which is necessary for erythroid BCL11A expression. Here we develop pooled clustered regularly interspaced palindromic repeat (CRISPR)-Cas9 guide RNA libraries to perform in situ saturating mutagenesis of the human and mouse enhancers. This approach reveals critical minimal features and discrete vulnerabilities of these enhancers. Despite conserved function of the composite enhancers, their architecture diverges. The crucial human sequences appear to be primate-specific. Through editing of primary human progenitors and mouse transgenesis, we validate the BCL11A erythroid enhancer as a target for fetal haemoglobin reinduction. The detailed enhancer map will inform therapeutic genome editing, and the screening approach described here is generally applicable to functional interrogation of non-coding genomic elements. A CRISPR-Cas9 approach is used to perform saturating mutagenesis of the human and mouse BCL11A enhancers, producing a map that reveals critical regions and specific vulnerabilities; BCL11A enhancer disruption is validated by CRISPR-Cas9 as a therapeutic strategy for inducing fetal haemoglobin by applying it in both mice and primary human erythroblast cells. BCL11A enhancer disruption analysed BCL11A is a transcriptional repressor that inhibits expression of fetal globin genes in adults, and is a potential therapeutic target for the treatment of β-globinopathies such as β-thalassemia and sickle cell disease. The enhancer of BCL11A is subject to common genetic variation associated with fetal hemoglobin level. Here, Daniel Bauer and colleagues use a CRISPR–Cas9 approach to perform saturation mutagenesis of the human and mouse BCL11A enhancers, producing a map that reveals critical regions and specific vulnerabilities. They validate BCL11A enhancer disruption by CRISPR–Cas9 as a therapeutic strategy for inducing fetal haemoglobin by applying it in both mice and primary human erythroblast cells.